Consumption of barracuda in the Caribbean Sea linked to ciguatera fish poisoning among Filipino seafarers - Niño Rebato; Vikki Carr de los Reyes; Ma. Nemia Sucaldito; Flor D'Lynn Gallardo; Julius Erving Ballera; Irma Asuncion; Kenneth Hartigan-Go (World Health Organization Regional Office for the Western Pacific, 2018)
Introduction: Ciguatera fish poisoning (CFP) is common in tropical and subtropical waters. On 13 November 2015, eight Filipino seafarers from a cargo ship sailing in the Caribbean Sea experienced a range of symptoms after consuming a barracuda. Upon their return to the Philippines, an investigation was conducted to describe the cases. Methods: A case-series was conducted. A CFP case was defined as a previously well individual on the ship who developed at least one gastrointestinal symptom and at least one neurologic manifestation after eating barracuda on 13 November 2015. All cases were admitted to hospital in Manila, Philippines and were interviewed using a standard questionnaire. Urine and serum samples of cases were collected for ciguatoxin (CTX) testing by radiological and receptor-binding assay. Results: Eight of the 25 seafarers on the ship ate the barracuda; all eight met the CFP case definition. The age of cases ranged from 37 to 58 years (median: 47 years) and all were males. Onset of symptoms ranged from 1 to 3 hours (median: 2 hours) from the time of ingestion of the barracuda. All cases experienced gastrointestinal (nausea, vomiting, diarrhoea) and neurologic (temperature allodynia, itchiness) symptoms but no cardiovascular manifestations. Urine and serum specimens of all eight cases showed CTX below the detection limit. Discussion: The Philippines Epidemiology Bureau recommended that the Philippine Maritime Authority include CTX poisoning and its health risks in seafarers' training to prevent future cases of CFP. The Event-based Surveillance and Response system will continue to provide a mechanism for the reporting and appropriate management of CFP cases.